2023
DOI: 10.3389/fimmu.2023.1111072
|View full text |Cite
|
Sign up to set email alerts
|

Host M-CSF induced gene expression drives changes in susceptible and resistant mice-derived BMdMs upon Leishmania major infection

Abstract: Leishmaniases are a group of diseases with different clinical manifestations. Macrophage-Leishmania interactions are central to the course of the infection. The outcome of the disease depends not only on the pathogenicity and virulence of the parasite, but also on the activation state, the genetic background, and the underlying complex interaction networks operative in the host macrophages. Mouse models, with mice strains having contrasting behavior in response to parasite infection, have been very helpful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Understanding the complex interplay between Leishmania and the host immune system is crucial for developing effective treatments against leishmaniasis. Previous studies have identified various molecular pathways and signaling networks involved in the immune response to Leishmania infection [5][6][7]. For instance, Fakiola et al utilized whole blood transcriptional profiles associated with asymptomatic infection, active disease, and treated cases of visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the complex interplay between Leishmania and the host immune system is crucial for developing effective treatments against leishmaniasis. Previous studies have identified various molecular pathways and signaling networks involved in the immune response to Leishmania infection [5][6][7]. For instance, Fakiola et al utilized whole blood transcriptional profiles associated with asymptomatic infection, active disease, and treated cases of visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
“…[6]. By analyzing dynamic transcriptome data obtained from Leishmania major infected bone marrow-derived macrophages from resistant and susceptible mice, Bouabid et al identified DEGs that may account for the differences in the immune response to infection between the two strains [7].…”
Section: Introductionmentioning
confidence: 99%